RNA Structure Determination : Methods and Protocols - Mathews, David H.; Turner, Douglas H. (Methods in molecular biology., 2016)
This volume provides protocols and procedures for determining and modeling RNA structure. Chapters guide the reader through protocols for RNA secondary structure prediction, single sequence modeling, Crumple, RNAstructure to model conserved secondary structures with multiple homologs, the prediction of bimolecular secondary structures with RNAstructure, STarMir, protocols for structure mapping, mapping data to constrain or restrain RNA secondary structure prediction with RNAstructure, unassigned NMR resonances, modeling protocols for Rosetta FARFAR, RNAComposer , ModeRNA, and MC-Fold. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. < Authoritative and Practical, RNA Structure Determination: Methods and Protocols aims to ensure successful results in the further study of this vital field.